Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Weda Reef Dan Rainforest Resort Terhadap Pariwisata Dan Ekowisatadi Kabupaten Halmahera Tengah - Anhar Drakel (Peneliti.net, 2022)
This study aims: The factors that influence the income of Weda Reef and Rainforest Resort on ecotourism tourism in Central Halmahera Regency. Data analysis includes: 1) Reliability test analysis, 3) Reliability test analysis 4). Linearity Test Analysis 5). multiple linear regression analysis, 4) Chi-Square analysis. From these results obtained 1). The number of tourist visitors does not show a significant relationship to the facilities, this can be seen from the regression coefficient of 0.878 and the standard error of 1.226. The null hypothesis is accepted because p. a value of 0.50 which is greater than the 0.05 significance level, because it is in accordance with the theory of trimming the path of the number of tourist visitors to Weda Reef and Rainforest Resort being discarded or omitted. 2). The number of tourist visitors does not show a significant relationship to the number of rooms, this can be seen from the regression coefficient of 0.011 and the standard error of 0.067. The null hypothesis is accepted because p. a value of 0.953 which is greater than the 0.05 significance level, because it is in accordance with the theory of trimming the path of the number of tourist visitors to Weda Reef and Rainforest Resort being discarded or omitted. 3). Facilities show a significant relationship to the number of rooms, this can be seen from the regression coefficient of 0.984 and standard error of 0.295. The null hypothesis is accepted because p. value of 0.026 which is greater than the 0.05 level of significance, because it is in accordance with the theory of trimming the path of the number of tourist visitors to Weda Reef and Rainforest Resort. 4). The number of tourist visits has a positive and significant effect on the acceptance of tourist attraction fees, this can be seen from the regression coefficient value of 1,000, and the standard error of and the value of p. value of 0.000 which is less than the 0.05 significance level, then the facility has a significant effect on income.